Pengaruh Citra Merek, Desain Produk Dan Harga Terhadap Keputusan Pembelian Di Lubuk Pandan Kec. 2x11 Enam Lingkung Kab. Padang Pariaman - Maria Magdalena; Armansyah Armansyah (JURNAL PUNDI, 2022)
The purpose of this study is to provide empirical evidence of the influence of Brand Image, Product Design and Price on the Purchase Decision of "Xiomi" Mobile Phones in Lubuk Pandan Kec.2x11 Enam Lingkung Kab. Pariaman Padang. The population in this study is the people of Lubuk Pandan Kec.2x11 Enam  lingkung Kab. Pariaman Padang. Accidental sampling technique is a sampling technique used in this study. The sample in this study were mobile phone buyers from Lubuk Pandan sub-district 2x11 Enam Lingkung Kabupaten Padang Pariaman who had predetermined criteria or characteristics. The number of respondents who can be used in this study are 87 people in Lubuk Pandan Kec.2X11 Enam Lingkung Kab. Pariaman Padang. Price has no effect on purchasing decisions. This type of research is quantitative research. It is hoped that mobile phone shops will first see the brand image, product design and price so that people who want to buy products feel comfortable and make good decisions when making purchases. Keywords: Brand Image, Product Design, Price and Purchase Decision